La seringue et la gâchette - Thomas Lequeu (Les Cahiers de l'École du Louvre)
Although the movies of the second half of Jean-Pierre Melville’s career are often referred to in the literature as “men’s films”, Un flic (1972), his last work, is the one that most openly questions the issue of gender. The detective story becomes the pretext to present a gallery of characters with murky sexual identities and attributions. Thus, the dichotomy between the character of Cathy, a femme fatale and a murderer in a lab coat, and that of Gaby, a transsexual police informer made to suffer humiliation and beatings, matches the parallel between the cop and the mobster. This detailed study of the mechanisms of violence that underlie the film questions its ambiguity, while also ascribing it as an element of the gender-based morality that runs through the director’s filmography.